Metal as evolutionary factor: Culturological comprehension - Khazbulatov, A. R. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2016)
The article is devoted to the culturological comprehension of metal ingeneral and art in particular, as a cultural phenomenon, which occupies an important place in the spiritual and material evolution of mankind. The author believes that in the course of humane volution, as well as in the arts and crafts, metal occupies a fundamental place. Mastering the art processing and metal is not just a historical stage, but the transition to a completely different level of consciousness. This article will consider the metal as a material having a specific technical characteristics and meaning, there fore, is of particular value in the context of the preservation of cultural heritage.